2018
DOI: 10.1590/1677-5449.008617
|View full text |Cite
|
Sign up to set email alerts
|

Aneurisma da artéria isquiática persistente: relato de caso de tratamento endovascular

Abstract: Resumo A persistência da artéria isquiática é uma anomalia vascular congênita rara cuja principal complicação é a dilatação aneurismática. O quadro clínico pode incluir sintomas decorrentes da dilatação arterial e da isquemia, causada por trombose ou embolização distal. O tratamento dessa afecção rara conta com opções diversas que abrangem desde a ligadura do aneurisma até a correção endovascular. O presente relato descreve o caso de uma paciente do sexo feminino com queixa de tumoração pulsátil na região glút… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…16 Currently, there is no good guidance for decision-making by the operator, 1 and therefore the treatment of PSAA varies according to symptoms and the clinical presentation of the patient. 7 In general, when trying to decide to treat PSAA, the presence of any thrombus inside the aneurysmal lumen must be taken into consideration, as PSAAs have been associated with ischemia due to distal embolization more commonly than actual aneurysm rupture. 25,32 Thereby, Ahn et al suggested that there should be no size threshold for elective PSAA repair performed either endovascularly or surgically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Currently, there is no good guidance for decision-making by the operator, 1 and therefore the treatment of PSAA varies according to symptoms and the clinical presentation of the patient. 7 In general, when trying to decide to treat PSAA, the presence of any thrombus inside the aneurysmal lumen must be taken into consideration, as PSAAs have been associated with ischemia due to distal embolization more commonly than actual aneurysm rupture. 25,32 Thereby, Ahn et al suggested that there should be no size threshold for elective PSAA repair performed either endovascularly or surgically.…”
Section: Discussionmentioning
confidence: 99%
“…Ninety-three studies after duplicates removed were identified, and 23 were screened out for full-text evaluation. Finally, 15 case reports 1,4,[6][7][8][9][10][11][12][13][14][15][16][17][18] been published between 2001 and 2018 eventually fulfilled the inclusion criteria and were included in this systematic review as shown in the flow diagram ( Figure 1). The median age of the included patients was 64 years old (47-88 years old).…”
Section: Characteristics Of the Included Studies And Patientsmentioning
confidence: 99%